REVIEW KINERJA STRUKTUR ATAS GEDUNG RESKRIMSUS POLDA JAWA TIMUR BERDASARKAN PERATURAN SNI 1726-2019 DAN SNI 2847-2019 - Ilham Abdul Aburrokhim; Bantot Sutriono; Masca Indra Triana (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
Indonesia is an area located on the path between the Pacific earthquake and the path of the Asian earthquake and at the meeting of four tectonic plates namely the Eurasian, Indo-Australian, Pacific, Philippine plates, called the Ring of Fire. The movement between these plates causes frequent earthquakes that cause forces that propagate into the waveform. This wave causes the ground surface and above to experience vibrations. So that the occurrence of tremors due to the earthquake can have the opportunity to cause damage, loss of property and casualties in the area traversed by the earthquake wave. Material damage and losses that usually occur due to earthquakes are damage to infrastructure and building construction. So in that case to find out the conditions when which are the performance conditions and structural strength of a building. So the researcher conducted a Reveiw on the object of the East Java Police Reskrimsus office with the Pushover method which is one of the methods of a